2014
DOI: 10.1128/jb.01997-14
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Pseudomonas aeruginosa Global Regulator AmpR

Abstract: Pseudomonas aeruginosa is a dreaded pathogen in many clinical settings. Its inherent and acquired antibiotic resistance thwarts therapy. In particular, derepression of the AmpC ␤-lactamase is a common mechanism of ␤-lactam resistance among clinical isolates. The inducible expression of ampC is controlled by the global LysR-type transcriptional regulator (LTTR) AmpR. In the present study, we investigated the genetic and structural elements that are important for ampC induction. Specifically, the ampC (P ampC ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 86 publications
1
45
0
Order By: Relevance
“…One of the targets might be the transcriptional regulator AmpR, a potential inner membrane-associated protein (58). This hypothesis is supported by the observations that in the presence of ␤-lactams, the ⌬rpoN mutant stimulated a significant increase in the levels of the ampR gene and the gene encoding ␤-lactamase, ampC (58), suggesting that this increase in ampR and ampC levels might aid in explaining the carbapenem-tolerant phenotype of the ⌬rpoN mutant. Additionally, the ⌬ampR mutant exerted a negative effect on the expression of the major QS regulators LasR, RhlR, PqsR, and PQS and the pyochelin and pyoverdine genes (59).…”
Section: Discussionsupporting
confidence: 59%
“…One of the targets might be the transcriptional regulator AmpR, a potential inner membrane-associated protein (58). This hypothesis is supported by the observations that in the presence of ␤-lactams, the ⌬rpoN mutant stimulated a significant increase in the levels of the ampR gene and the gene encoding ␤-lactamase, ampC (58), suggesting that this increase in ampR and ampC levels might aid in explaining the carbapenem-tolerant phenotype of the ⌬rpoN mutant. Additionally, the ⌬ampR mutant exerted a negative effect on the expression of the major QS regulators LasR, RhlR, PqsR, and PQS and the pyochelin and pyoverdine genes (59).…”
Section: Discussionsupporting
confidence: 59%
“…In addition, new players such as ampP, ampDh2 and ampDh3 have been identified in P. aeruginosa [139,151]. Moreover, the localization of P. aeruginosa AmpR as an inner membrane protein with the helix-turn-helix domain in the cytoplasm and effector-binding domain in the periplasm leads to unique questions as to how the effector molecules are transported to their binding sites on AmpR [212].…”
Section: Cell-wall Recycling and Antibiotic Resistancementioning
confidence: 99%
“…In Pseudomonas aeruginosa, several works showed that AmpR is a global transcriptional regulator. It is a potential membrane-associated dimer that regulates genes involved in virulence, quorum sensing, and stress response (14)(15)(16)(17)(18). In addition, three AmpD enzymes have been found in P. aeruginosa.…”
mentioning
confidence: 99%